Pengaruh Persepsi Resiko, Kemudahan Penggunaan dan Kepercayaan Terhadap Kepuasan Serta Dampaknya pada Niat Beli Ulang: Studi pada Aplikasi Shopee di Kota Semarang - Fadel Muhamad Rizal Zuhri; Endang Tjahjaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
E-commerce is currently growing very rapidly, especially Shopee. Many clients are making online purchases through the platform. The reason for this study is to assess the effect of visible risk, level of convenience in use, and the level of trust on the satisfaction of fair and square buyers and its effect on the desire to buy and square and their effect on the desire to repurchase. again. In this search considering 104 respondents using the Shopee aplication in the Semarang area. Testing is assisted by using quantitative techniques through a purposive examination approach. purposive examination. Information examination is carried out through a series of tests based on SPSS measurements consisting of the Shopee ecommerce client itself, and speculation testing using the t test and f test. speculation testing using the t test and f test. Test results show that risk perception does not affect customer satisfaction, user-friendliness affects customer satisfaction, trust affects satisfied buyers as well as consumer satisfaction basically affects the desire to repurchas to repurchase.